Legitimizing work: telework and the gendered reification of the work-nonwork dichotomy. - Mirchandani, Kiran (Canadian Review of Sociology & Anthropology, 1999)
The writer discusses the reasons why teleworkers, who are salaried employees working at home rather than at a central office, continue to need to maintain a division between their private and public lives. She draws upon qualitative interviews with male and female teleworkers to explore gender differences in the ways in which they organize their lives in terms of the public/work—private/nonwork dichotomy. She investigates the mechanisms that necessitate the reification of this dichotomy. She finds that teleworkers are keen to maintain the division between work and nonwork in order to ensure that their paid work is seen as legitimate. She asserts that the resilience of the rhetoric of the separate spheres lies in the fact that women and men need to define nonwork as different, private, and less important in order to legitimize the work they do. She states that teleworkers thus resist the widening of the definition of work to include domestic work and childcare because they recognize that such a widening can result in a devaluation of their paid work rather than a reevaluation of their domestic work.